Peptide vaccine formulations with structurally distinct STING agonist drugamers induce discrete, efficacious antitumor responses - Kefan Song; Dinh Chuong Nguyen; Yonghui Wang; Simbarashe Jokonya; Omeed Yazdani; Drew L. Sellers; Patrick S. Stayton; Suzie H. Pun (Proceedings of the National Academy of Sciences, 2025)
Peptide therapeutic cancer vaccines are an attractive treatment modality for their safety and manufacturability but have been hindered in clinical translation by low immunogenicity and insufficient CD8 + T cell activation. We developed virus-inspired polymers for endosomal release (VIPER) to address systemic and intracellular delivery obstacles, but durable antitumor immunity remained elusive. Adjuvants stimulating innate immunity, such as stimulator of interferon genes (STING) agonists, can enhance vaccine potency but risks systemic toxicity and improper immune activation. We developed STING “drugamers” with cathepsin-cleavable linkers and dendritic cell (DC)-targeting moieties for intracellular delivery of STING agonists to DCs. We explored two different STING drugamer structures: a hydrophilic statistical polymer “polySTING” and a diblock polymer “NPSTING” that forms into nanoparticles. PolySTING achieved higher systemic STING agonist delivery, whereas NPSTING is more efficient in delivering STING agonists into inguinal lymph nodes (LNs). Both drugamer platforms enhanced STING activation and DC maturation compared to the free drug. When combined with VIPER, NPSTING generated more antigen-presenting DCs in the LNs and more antigen-responsive CD8 + T cells in the spleens, whereas polySTING generated more tumor-infiltrating CD8 + T cells and CD8 + DCs. Both VIPER–STING drugamer platforms demonstrated efficacy in a B16-OVA melanoma model and a MC38 colon cancer model. Combination treatment with anti-PD-1 immune checkpoint inhibitor results in tumor remission and tumor immunity in a subset of mice. This study highlights how an endosomolytic peptide vaccine platform combined with two structurally different drugamers induce superior antitumor responses through distinctive mechanisms.